Exosomes containing long non-coding RNA AGAP2-AS1 promote the differentiation of CD4+ T cells through the miR-424-5p/SGK1 axis in psoriasis - Yuan, Ziqi; Zeng, Xue; Zhang, Xiwei; Xia, Chenglai; Peng, Xuebiao (Frontiers in Genetics, 2025)
BackgroundLong non-coding RNAs (lncRNAs) have been implicated in the pathogenesis of autoimmune diseases. Our previous research demonstrated that AGAP2-AS1 in keratinocytes is involved in the pathogenesis of psoriasis, but its effect on CD4+ T cell differentiation remains unclear.MethodsExosomes were extracted from HaCaT cells using a reagent kit and verified by TEM (Transmission Electron Microscope), NTA (Nanoparticle Tracking Analysis), and Western Blot. We incubated exosomes with CD4+ T cells and detected the distribution of AGAP2-AS1 by fluorescence microscopy. Flow cytometry and ELISA were used to detect CD4+ T cell differentiation. In addition, the relationship between AGAP2-AS1/miR-424-5p/SGK1 and its effect on CD4+ T cell differentiation were confirmed by bioinformatics analysis, dual luciferase reporter gene experiments, quantitative real-time PCR, flow cytometry, and ELISA.ResultsWe found that exosomes derived from TNF-α-treated HaCaTs were able to deliver AGAP2-AS1 to CD4+ T cells, promoting Th1 and Th17 differentiation. In CD4+ T cells, AGAP2-AS1 promotes Th1 and Th17 differentiation via the miR-424-5p/SGK1 axis.ConclusionPsoriatic HaCaTs deliver AGAP2-AS1 to CD4+ T cells via exosomes, inducing Th1 and Th17 differentiation through the miR-424-5p/SGK1 axis, thereby promoting the progression of psoriasis. These findings provide novel insights into the pathogenesis of psoriasis and potential therapeutic targets.